2015
DOI: 10.1371/journal.pone.0128624
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a 4977-bp Fragment in the Mitochondrial Genome Is Associated with Mitochondrial Disease Severity

Abstract: Large deletions in mitochondrial DNA (mtDNA) may be involved in the pathogenesis of mitochondrial disease. In this study, we investigated the relationship between a 4,977-bp deletion in the mitochondrial genome (ΔmtDNA4977) and the severity of clinical symptoms in patients with mitochondrial disease lacking known point mutations. A total of 160 patients with mitochondrial disease and 101 healthy controls were recruited for this study. The copy numbers of ΔmtDNA4977 and wild-type mtDNA were determined by real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Our results showed that the 4977bp deletion was observed in 18.6% (8/43) of NAFLD patients, whereas this deletion was not detected in any of liver tissue samples obtained from the 20 control subjects. Several studies have found the mtDNA 4,977-bp deletion in various types of diseases (16, 17). The exact cause of the increased mtDNA deletion levels in different tissues remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the 4977bp deletion was observed in 18.6% (8/43) of NAFLD patients, whereas this deletion was not detected in any of liver tissue samples obtained from the 20 control subjects. Several studies have found the mtDNA 4,977-bp deletion in various types of diseases (16, 17). The exact cause of the increased mtDNA deletion levels in different tissues remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The 4,977 bp deletion is located between nucleotides 8,469 and 13,447 and includes several essential oxidative phosphorylation genes encoding ATPase6/8, cytochrome oxidase III, NADH dehydrogenase subunit 3 (ND3), ND4, and ND5. This large deletion is the most common deletion in the mitochondrial genome that has been detected in several types of human diseases (16, 17). Moreover, it has been suggested that variations in mtDNA copy numbers may also be associated with some disorders.…”
Section: Introductionmentioning
confidence: 99%
“…One of the best-described large-scale mtDNA deletions is the specific 4977 bp deletion (mtDNA 4977 ), which occurs between nucleotides 8470 and 13447 and eliminates seven genes encoding four subunits of Complex I (ND3, ND4, ND4L, partial ND5), one subunit of Complex IV (COIII) and two subunits of ATP-synthase (ATP6 and partial ATP8); all of which are crucial for OXPHOS (depicted in Figure 3). Accordingly, mtDNA 4977 has been linked to a spectrum of disorders, including heart disease, different forms of cancer and mitochondrial diseases [143][144][145][146]. Notably, this mutation has also been reported to accumulate in different human tissues as a consequence of natural aging [147].…”
Section: Sperm Dna Modificationsmentioning
confidence: 99%
“…The absolute mtDNA copy number was measured by a quantitative real-time polymerase chain reaction (PCR)-based method as previously described. [ 12 17 ] mtDNA was quantified as the ratio of a mitochondrial gene copy number ( ND1 ) to a single-copy nuclear gene (human β-globin gene, HBB ). mtDNA copy number per cell was calculated by the formula 2× ND1 / HBB .…”
Section: Ethodsmentioning
confidence: 99%